Role of the kdpDE Regulatory Operon of Mycobacterium tuberculosis in Modulating Bacterial Growth in vitro - Cholo, Moloko C.; Matjokotja, Maborwa T.; Osman, Ayman G.; Anderson, Ronald (Frontiers in Genetics, 2021)
Bacteria use K+-uptake transporters differentially for adaptation in varying growth conditions. In Mycobacterium tuberculosis, two K+-uptake systems, the Trk comprising the CeoB and CeoC proteins and the Kdp consisting of the two-component system (TCS), KdpDE and KdpFABC, have been characterized, but their selective utilization during bacterial growth has not been completely explored. In the current study, the roles of the M. tuberculosis KdpDE regulatory system alone and in association with the Trk transporters in bacterial growth were investigated by evaluating the growth of M. tuberculosis KdpDE-deletion and KdpDE/Trk (KT)-double knockout mutant strains in planktonic culture under standard growth conditions. The KT-double knockout mutant strain was first constructed using homologous recombination procedures and was evaluated together with the KdpDE-deletion mutant and the wild-type (WT) strains with respect to their rates of growth, K+-uptake efficiencies, and K+-transporter gene expression during planktonic growth. During growth at optimal K+ concentrations and pH levels, selective deletion of the TCS KdpDE (KdpDE-deletion mutant) led to attenuation in bacterial growth and an increase in bacterial K+-uptake efficiency, as well as dysregulated expression of the kdpFABC and trk genes. Deletion of both the KdpDE and the Trk systems (KT-double knockout) also led to severely attenuated bacterial growth, as well as an increase in bacterial K+-uptake efficiency. These results demonstrate that the KdpDE regulatory system plays a key role during bacterial growth by regulating K+ uptake via modulation of the expression and activities of both the KdpFABC and Trk systems and is important for bacterial growth possibly by preventing cytoplasmic K+ overload